A visit to the Mountain of Guerrero; first records of medium and large mammals in Atlixtac, Guerrero, México - Rodríguez-Ruiz, Rodolfo; Ramírez Barrios, Rocío; Pereyra Cortés, Beatriz; Bailón Miranda, Javier; Sánchez Castro, Carlos; Monroy-Vilchis, Octavio (Therya Notes, 2023)
The Guerrero state is an important area for its high diversity of mammals. However, there are few studies documenting this diversity in the state. Due to the above, the diversity of terrestrial mammals in the Mountain region of the Atlixtac, Guerrero was analyzed. During September 2021 to March 2022 the community of Atlixtac, Guerrero was visited, camera-traps were placed, and walks were conducted. The information obtained was organized and analyzed for abundance and diversity. Fifteen species distributed in 10 families were recorded; of these, 2 species are under protection in the NOM-059-SEMARNAT-2010; Leopardus wiedii by photo-trapping (n = 3) and Herpailurus yagouaroundi (n = 1) by hunting report. The study area is important for mammals in the Guerrero state, the distribution and knowledge of species such as L. wiedii, H. yagouaroundi and S. angustifrons are expanded. It is important to increase monitoring in the Mountain region of Guerrero, the results obtained indicate a high probability of increasing the number of species in the state. The study area is of ecological importance because it is located within the Sierra Madre del Sur and connects with the Balsas Basin and serving as a biological corridor for various species of mammals.